PERLINDUNGAN HUKUM TERHADAP PEMILIKAN HAK ATAS TANAH DENGAN TERBITNYA SERTIFIKAT GANDA - Tiani, Aulia Sekar; Susilowati, Rini Endang; Dakum, Dakum (JURNAL DWIJA KUSUMA, 2025)
To protect and guarantee legal provisions, the government requires registration of land rights as regulated by Government Regulation No. 24 of 1997. The publication of two land certificates on a parcel of land can lead to a legal case such as in Magelang City. The approach used is a qualitative approach to legal protection of control and ownership of land rights, on the issuance of multiple certificates in one object of the same land, followed by qualitative descriptive analysis of primary data from notaries and document review. The results of this study are the factors that cause the occurrence of multiple land certificates, namely the mistake of the landowner, inaccuracy and lack of accuracy of land officers when conducting examinations and studies of the proposed land. Legal protection that can be done by the government to prevent the issuance of multiple certificates involves synchronization and completeness of legal products, as well as increased integrity in land registration.